2011
DOI: 10.1016/j.jcf.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment intensity and characteristics of MRSA infection in CF

Abstract: Patients with chronic MRSA are treated more intensely than age, gender and Pseudomonas aeruginosa matched MSSA-positive patients but clinical characteristics within MRSA patients vary depending on MRSA types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
5
21
1
Order By: Relevance
“…[27][28][29] Furthermore, older patients with CF are more likely to harbor hospitalassociated clones, suggesting acquisition prior to the widespread onset of CA MRSA. 30 Support for acquisition of MRSA in health-care settings is provided by a report that found that more stringent infection prevention and control strategies, which included universal contact precautions, significantly reduced MRSA in a pediatric CF clinic. 31 Studies to find effective therapeutic approaches to eradication are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Furthermore, older patients with CF are more likely to harbor hospitalassociated clones, suggesting acquisition prior to the widespread onset of CA MRSA. 30 Support for acquisition of MRSA in health-care settings is provided by a report that found that more stringent infection prevention and control strategies, which included universal contact precautions, significantly reduced MRSA in a pediatric CF clinic. 31 Studies to find effective therapeutic approaches to eradication are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…FEV 1 percent predicted did not differ among patients colonized with MRSA or with MSSA, even after adjusting for Pseudomonas colonization, age, and gender. While MRSA patients did require more pulmonary maintenance therapy (i.e., mucolytics, inhaled steroids, and chronic antimicrobial suppressive therapy), they did not require a greater number of antibiotic courses than did MSSA patients (65). In another cohort, MRSA-colonized patients had a faster decline in lung function even before acquisition of MRSA, suggesting that MRSA was not the cause of this decline but may have been a proxy marker (66).…”
Section: Cystic Fibrosis (Cf) Mrsa Carriage and Disease Progressionmentioning
confidence: 92%
“…219 The latter group consisted of younger individuals. In a multicenter study conducted in the United States from 2008 to 2010, SCCmec type II strains were more common than SCCmec type IV strains, accounting for 71% of MRSA isolates, and 84% of SCCmec type IV strains that harbored Panton-Valentine leukocidin were USA300, the most common community-associated MRSA clone.…”
Section: Iiia3 Other Gram-negative Bacteriamentioning
confidence: 99%